(untitled) (Orinoquia, 2015)
Urban contamination produced by city dynamics has aroused interest during the last few years. This study involved using the (Igeo) geoaccumulation index for identifying the contamination produced by heavy metals (i.e. Pb, Cd, Cu, Cr, Ni, Zn) in three sectors of the city of Villavicencio; heavy metal concentration was determined by atomic absorption spectroscopy (AAS). It was found that the greatest concentrations of these metals, especially lead, occurred in the Porvenir sector of the city, this being an area associated with rudimentary car repair and wrecker activity. Road deposited sediment (RDS) is a factor having an impact on cities’ increased growth and dynamics and could be responsible for many environmental issues. Key words: Heavy metal; urban pollution; lead concentration in road deposited sediment (RDS).